ERKIN VAKHIDOV MASTER OF PSYCHIATRY (Academicia Globe: Inderscience Research, 2021)
The work of Erkin Vakhidov, one of the great representatives of Uzbek literature of the 20th century, is unique. The principle of such noble ideas as nationalism, humanity, philosophy, history, which embrace his work, involuntarily invites the reader to a poetic observation. One of the main features of the poet's work is to express the reality of life in all its complexity and fullness, with its contradictions, boldly raise acute social issues, artistically depict the freedom of the spiritual and physical spirit. The famous poet, statesman and public figure, Hero of Uzbekistan Erkin Vakhidov, who made an unforgettable contribution to the development of Uzbek literature and culture, did a lot to educate the younger generation in the spirit of love and devotion to the Motherland, Fatherland and Motherland. Universal human values and perpetuate the memory of the poet.